Interaction Design / Beyond Human-Computer Interaction - Preece Jenny; Rogers Yvonne; Sharp Helen (John Wiley & Sons, Ltd, 2011)
This book offers a cross-disciplinary, practical and process-oriented approach, showing not just what principles ought to apply to interaction design, but crucially how they can be applied. What is Interaction Design, Understanding and Conceptualizing Interaction, Cognitive Aspects, Social Interaction, Emotional Interaction, Interfaces, Data Gathering, Data Analysis and Interpretation and Presentation, The Process of Interaction Design, Establishing Requirements, Design and Prototyping and Construction, Introducing Evaluation, An Evaluation Framework, Evaluation Studies: From Controlled to Natural Settings, References, Index.